Losing Eden : why our minds need the wild - Jones, Lucy (Journalist) (Penguin Books, 2021)
Today many of us live indoor lives, disconnected from the natural world as never before. And yet nature remains deeply ingrained in our language, culture and consciousness. For centuries, we have acted on an intuitive sense that we need communion with the wild to feel well. Now, in the moment of our great migration away from the rest of nature, more and more scientific evidence is emerging to confirm its place at the heart of our psychological wellbeing. So what happens, asks acclaimed journalist Lucy Jones, as we lose our bond with the natural world--might we also be losing part of ourselves? Delicately observed and rigorously researched, Losing Eden is an enthralling journey through this new research, exploring how and why connecting with the living world can so drastically affect our health. Travelling from forest schools in East London, to the Svalbard Global Seed Vault, via Poland's primeval woodlands, Californian laboratories and ecotherapists' couches, Jones takes us to the cutting edge of human biology, neuroscience and psychology, and discovers new ways of understanding our increasingly dysfunctional relationship with the earth. Urgent and uplifting, Losing Eden is a rallying cry for a wilder way of life - for finding asylum in the soil and joy in the trees - which might just help us to save the living planet, as well as ourselves, from a future of ecological grief.